Geobacter species enhances pit depth on 304L stainless steel in a medium lacking with electron donor - Mehanna, M.; Basseguy, R.; Delia, M.; Gubner, Rolf; Sathirachinda, N.; Bergel, A. (Elsevier, 2009)
Geobacter sulfurreducens bacteria increased the open circuit potential of 304L stainless steel by around 320 mV in only a few hours after inoculation. This represents a significant increase in the corrosion risk. In contrast, the oxidation of acetate, which is catalysed by well-established biofilms, shifted the pitting potential towards positive values. In acetate-lacking media, pitting occurred with and without bacteria in the same range of potential values, but the presence of bacteria drastically increased the size of pits. AFM showed pits more than 10 times broader and deeper due to the presence of bacteria.In the absence of acetate, the masking effect due to acetate oxidation disappeared and the full corrosive effect of the biofilm was revealed.This also Fully explains why pitting was predominantly observed close to surface areas where bacterial settlement was the densest.